2019
DOI: 10.3390/ijerph16111951
|View full text |Cite
|
Sign up to set email alerts
|

Housing Design and Community Care: How Home Modifications Reduce Care Needs of Older People and People with Disability

Abstract: The extent to which housing design can minimise levels of community caregiving has remained largely unmeasured. This paper reports the potential for home modifications to reduce caregiving in the peoples’ homes, particularly older people and people with a disability. It contributes to new knowledge in understanding how housing can play a role in community caregiving and acknowledges the role of the built environment in managing care levels in ageing societies. This paper analyses self-reported care data from 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 47 publications
0
31
0
Order By: Relevance
“…Home modifications may also potentially prolong independence at home, or in some cases, delay institutionalization of older adults [11]. Additionally, people living with a disability at any age may benefit from home modifications [12]. Thus, home modifications may act as a bridge to emphasize active aging through a life course perspective [4].…”
Section: Home Modifications and Aging-in-placementioning
confidence: 99%
“…Home modifications may also potentially prolong independence at home, or in some cases, delay institutionalization of older adults [11]. Additionally, people living with a disability at any age may benefit from home modifications [12]. Thus, home modifications may act as a bridge to emphasize active aging through a life course perspective [4].…”
Section: Home Modifications and Aging-in-placementioning
confidence: 99%
“…Even if benefits can be achieved by adopting either standard or personalized modifications [97], the types of interventions and their impact on wellbeing are highly individual [104]. There is a consensus in the literature on the several benefits arising from home modifications: Improving accessibility, preventing falls, promoting safety, reducing difficulty in performing everyday life tasks, and reducing the need for health care [38,67,69,97,104,[109][110][111]. However, to be fully effective, interventions on dwellings must be combined with other strategies such as fall-prevention programs [85,110].…”
Section: Modification For Accessibilitymentioning
confidence: 99%
“…A number of studies [35][36][37] have reported that housing adaptations have improved health, independence and quality of life in later life. Beyond health and independence, several other studies [38][39][40] have further found that environmental adaptations have reduced older people's need for support from family caregivers and have lessened the strain on family relationships. Because of their key role in preventing falls, avoiding hospital admission and reducing domiciliary care, housing adaptations have brought significant savings to the National Health Service (NHS) services, home care costs and social services budgets [41][42][43].…”
Section: Introductionmentioning
confidence: 99%